Establishing an Elective Rotation Director and Its Effect on Elective Opportunities and Satisfaction - Janicki, Adam J. (West J Emerg Med, 2020)
Elective rotations are valuable, allowing trainees to personalize their educational experience, focus on areas of weakness, and offer personal and professional development. Emergency medicine (EM) residency program elective rotations may be limited due to the absence of awareness of opportunities and administrative support. We sought to increase the breadth of elective rotation opportunities, improve residents’ satisfaction with their elective rotations, and enhance the opportunities for clinical training. To increase the breadth of our elective rotation opportunities, we established an elective rotation director—a dedicated faculty member to aid in elective planning and provide administrative support. This faculty member met with all residents during their second year, coordinated new electives with the graduate medical education office, and assisted with administrative tasks. Ten new rotations (two local, five domestic away, three international away) were established during the position’s first two years, increasing available rotations from nine to 19. A survey was sent to graduates of the program two years before and two years after the position was established to inquire about their elective experience. Of 64 graduates, 49 (76.6%) participated in the survey. Graduates exposed to the dedicated faculty member reported increased exposure to novel learning environments (p<0.001), improved wellness (p<0.001), and were more likely than pre-director graduates to choose the same elective rotation (p=0.006). Programs with multiple elective rotations may benefit more from this position, but additional resources may be needed given the associated increase in administrative time.